Demonstration of the blood-stage controlled human malaria infection model to assess efficacy of the Plasmodium falciparum AMA1 vaccine FMP2.1/AS01 - Payne, R; Milne, K; Elias, S; Edwards, N; Douglas, A; Brown, R; Silk, S; Biswas, S; Miura, K; Roberts, R; Rampling, T; Venkatraman, N; et al. (Oxford University Press, 2016)
Mosquito-bite controlled human malaria infection (CHMI) models have been widely used to assess efficacy of pre-erythrocytic vaccine candidates in small proof-of-concept Phase IIa clinical trials. Efficacy testing of blood-stage vaccines, however, has generally relied on larger-scale Phase IIb field trials in endemic populations. We report the use of a blood-stage Plasmodium falciparum CHMI model to assess blood-stage vaccine candidates using impact on the parasite multiplication rate (PMR) as the primary efficacy endpoint. Fifteen healthy UK adult volunteers were vaccinated with FMP2.1, a protein vaccine, based on the 3D7 clone sequence of apical membrane antigen 1 (AMA1), and formulated in AS01. Twelve vaccinees, and fifteen infectivity controls, subsequently underwent blood-stage CHMI. Parasitemia was monitored by quantitative real-time PCR, and PMR was modelled from these data. The FMP2.1/AS01 vaccine elicited anti-AMA1 T cell and serum antibody responses. Purified IgG showed functional growth inhibition activity against P. falciparum in vitro. There were no vaccine- or CHMI-related safety concerns. All volunteers developed blood-stage parasitemia, with no impact of the vaccine on PMR. FMP2.1/AS01 demonstrated no efficacy after blood-stage CHMI. However, the model induced highly reproducible infection in all volunteers, and will accelerate proof-of-concept testing of future blood-stage malaria vaccine candidates. NCT02044198.